2016
DOI: 10.1186/s40101-016-0092-8
|View full text |Cite|
|
Sign up to set email alerts
|

Characteristics of body composition and cardiometabolic risk of Japanese male heavyweight Judo athletes

Abstract: BackgroundThe purpose of this study was to clarify the characteristics of body composition and cardiometabolic risk of Japanese male heavyweight Judo athletes compared with heavyweight athletes of other sports.MethodsNineteen heavyweight Judo athletes (mean age, 20.4 ± 1.1 years), as well as 22 heavyweight (mean age, 21.5 ± 0.9 years) and 17 nonheavyweight (mean age, 21.1 ± 0.8 years) American football and Rugby football athletes in Japan participated in this study. Body composition was assessed by using dual-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 33 publications
(31 reference statements)
1
36
0
1
Order By: Relevance
“…Guo et al [ 3 ] found that professional athletes of strength sports in the heavier weight class usually have a higher prevalence of metabolic syndrome and its individual components, including central obesity. The same results were also observed in Japanese collegiate heavyweight Judo athletes and National Football League players [ 4 , 5 ].…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…Guo et al [ 3 ] found that professional athletes of strength sports in the heavier weight class usually have a higher prevalence of metabolic syndrome and its individual components, including central obesity. The same results were also observed in Japanese collegiate heavyweight Judo athletes and National Football League players [ 4 , 5 ].…”
Section: Introductionsupporting
confidence: 77%
“…Since athletes perform a large amount of exercise training, they usually have been regarded as a healthy model with a lower risk of cardiovascular disease. However, according to recent studies, the heavy athletes are usually at significantly higher risk of cardiovascular diseases [ 3 , 4 ]. To enhance athletic performance, American and rugby football athletes usually have the intent to consume more energy to gain more weight [ 32 ], which was suggested to lead to lipid accumulation in adiposity and ectopic tissues [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study is on judo, which is one of the popular martial arts. It can be seen clearly from the literature review that due to factors such as place and training systems, etc., martial arts with different systems and types have different physical and physiological characteristics (Chaabene et al, 2012;Murata et al, 2016;Ouergui et al, 2015). When respiratory functions (FVC, FEV1, FEV1/FVC, MVV, PEF) were analysed in our study, no statistically significant difference was found between EG and CG.…”
Section: Discussionmentioning
confidence: 99%
“…The offensive and defensive linemen of American football have both large amounts of fat-free mass as well as fat mass, resulting in greater body mass compared to athletes in other positions (Dengel et al, 2014;Morehen, Routledge, Twist, Morton, & Close, 2015). Notably, a study reported that there was an inverse correlation (r = −0.449) between body fat percentage and functional movement screen scores among college football players (Nicolozakes, Schneider, Roewer, Borchers, & Hewett, 2018). Further, there were inverse correlations between the percentage of body fat and high-speed movement performance in sprint and distance running (Abe et al, 2020;Alvero-Cruz et al, 2019;Herrmann et al, 2019), cycling (Schabort, Killian, St Clair Gibson, Hawley, & Noakes, 2000) and soccer matches (Radziminski, Szwarc, Padron-Cabo, & Jastrzebski, 2019).…”
Section: Introductionmentioning
confidence: 99%